Pengaruh Jumlah Penduduk Tenaga Kerja Dan Inflasi Terhadap Pertumbuhan Ekonomi Di Kabupaten Banyuwangi - ladi wajuba perdini fisabilillah; Dyan Puspita Sari (Jurnal Ekonomika : INDEPENDEN, 2021)
The factors that can be used to determine the ups and downs of economic growth are land and the natural resources in it, the population and the quality of the population and labor, the availability of capital goods and the level of technology used, the state of the social system and community behavior (Sukirno, 2013). ). If the population increases, it will certainly increase per capita income accompanied by an increase in the number of workers. Higher inflation will also cause domestic food prices to rise. This is the driving force behind the rise in wages in the industrial sector so that companies increase production costs. The author conducted a series of research activities to see how the influence of population, labor and inflation on economic growth in Banyuwangi Regency. The final result contained in this study is that partially the population has a significant negative effect on economic growth, in contrast to labor and inflation, the results of which do not significantly affect economic growth. However, with the results of simultaneous testing which shows that the variables of population, labor and inflation have no effect on economic growth.